Continuous and competitive circuit training: Methods to increase vo2max on young badminton player - Ariani, Luh Putu Tuti Ariani; Sudiana, I Ketut; Kusuma, Ketut Chandra Adinata (UIR Press, 2022)
The characteristic of badminton game is a sport with high intensity and intermitten actions. It takes the ability of a high level of physical condition, especially the level of VO2max to reach peak performance. There are many kinds of training method to increase VO2max, one of them is continuous circuit training and competitive circuit training. The purpose of this study is to discover the effect of continuous circuit training and competitive circuit training and to determine a more effective method to increase VO2max. This study is pre-experimental study with pre-test and post-test group design. The sample consisted of 60 badminton athletes in range of 9 – 12 years old and all of them were male. The instrument used to measure VO2max level was Multistage Fitness Test (MFT). VO2max data before and after treatement were analyzed with descriptive statistic and t-test on 5% significancy standard. Based on the data analysis, the following results were obtained: (1) There was a significant effect on the level of VO2max in the continuous circuit training group with sig 0.000 values; (2) There was a significant effect on the level of VO2max in the competitive circuit training group with values sig 0.000; and (3) There was no significant difference between the continuous circuit training group and the competitive circuit training group. So it can be concluded that continuous and competitive circuit training can increase the VO2max of young badminton players.